Acute myocardial infarction in a young woman on isotretinoin treatment. (15th February 2015) - Lorenzo, Natalia; Antuña, Paula; Dominguez, Lourdes; Rivero, Fernando; Bastante, Teresa; Alfonso, Fernando
Abstract: The use of isotretinoin has been associated with mild changes in the metabolic profile of adolescents. In very rare cases, a possible association with myocardial infarction, stroke and thromboembolic events has been reported. In this report we describe the potential association of isotretinoin with the occurrence of an acute myocardial infarction in a very young girl. OCT provided unique visualization of the culprit lesion.